THE EFFECT OF FECL3 AND LENGTH OF INCUBATION ON THE DEGRADATION OF LIGNOCELLULOSE FROM SENGON AND PINE WOODS USING SERPULA LACRYMANS - Irnia Nurika; Nur Hidayat; Nur Lailatul Rahma; Sakunda Anggarini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
ABSTRACTThe aim of this research is to determine the effect of FeCl3 affected to lignocelullosic degradation of Sengon and Pine wood residue by Serpula lacrymans during incubation. which was showed by the changing value of Total Soluble Phenols (TSP), Total Reducing Sugar (TRS), weight loss and pH extract. The experimental design used is a Factorial Block Randomized Design with three factors: the type of wood (K) (Sengon and Pinewoods), the concentration of FeCl3 (M) selected are 10, 30 and 50 µM and length of incubation (T): 0, 7, 14, 21, 28 and 35 days. The results revealed that the addition of FeCl3 on both types of woods during incubation did not give a significant impact on the value of TSP, TRS, weight loss and pH. The best treatment in TSP production is Sengon wood was incubated for 28 days (0.064 mg/g). While the greatest amount of total reducing sugars is Pinewood, incubated for 28 days in the amount of 36.58 mg/g. The best in percentage of weight loss is Pinewood, incubated for 28 days contains 33,98% with pH extract 4.14Keywords: biodegradation, lignocelullose, total soluble phenols, total reducing sugar.